Three-dimensional imaging assessment of anatomic invasion and volumetric considerations for chemo/radiotherapy-based laryngeal preservation in T3 larynx cancer. (April 2018) - Kamal, Mona; Ng, Sweet Ping; Eraj, Salman A.; Rock, Crosby D.; Pham, Brian; Messer, Jay A.; Garden, Adam S.; Morrison, William H.; Phan, Jack; Frank, Steven J.; El-Naggar, Adel K.; Johnson, Jason M.; et al.
Highlights: The extent of invasion of the primary tumor is an independent prognostic factor of the local control. The primary tumor volume and degree of vocal cord mobility didn't correlate with patient outcomes. Impaired airway at presentation requiring tracheotomy led to poor local control and survival. Baseline good performance status is an independent predictor of improved overall survival. Patients with multiple invasion may be counselled about close surveillance. Abstract: Objectives: To investigate the impact of 3-Diminsional (3D) tumor volume (TV) and extent of involvement of primary tumor on treatment outcomes in a large uniform cohort of T3 laryngeal carcinoma patients treated with nonsurgical laryngeal preservation strategies. Materials and Methods: The pretreatment contrast-enhanced computed tomography images of 90 patients with T3 laryngeal carcinoma were reviewed. Primary gross tumor volume (GTVp) was delineated to calculate the 3D TV and define the extent of invasion. Cartilage and soft tissue involvement was coded. The extent of invasion was dichotomized into non/limited invasion versus multiple invasion extension (MIE), and was subsequently correlated with survival outcomes. Results: The median TV was 6.6 cm 3 . Sixty-five patients had non/limited invasion, and 25 had MIE. Median follow-up for surviving patients was 52 months. The 5-year local control and overall survival rates for the whole cohort were 88% and 68%, respectively. There was no correlation between TV and survival outcomes. However, patients with non/limited invasion had better 5-year local control (LC) than those with MIE (95% vs 72%, p = .009) but did not have a significantly higher rate of overall survival (OS) (74% vs 67%, p = .327). In multivariate correlates of LC, MIE maintained statistical significance whereas baseline airway status showed a statistically significance trend with poor LC (p = .0087 and 0.06, respectively). Baseline good performance status was an independent predictor of improved OS (p = .03) in multivariate analysis. Conclusion: The extent of primary tumor invasion is an independent prognostic factor of LC of the disease after definitive radiotherapy in T3 larynx cancer.